Gastric Botulinum Toxin-A Application for Weight Loss Therapy - Şen, Ozan; Türkçapar, Ahmet Gökhan (Turkish Journal of Gastroenterology, 2021)
Background/Aims: In this study, our aim is to share the results of gastric botulinum toxin(BTX) application in individuals who are overweight or type 1 obese without comorbidity. Materials and Methods: 13 patients who were applied gastric BTX application for the first time were included in the study. A total of 300 U of BTX-A (Allergan Botox ®1 vial 100 U) is diluted with 8 ml of 0.9% NaCl saline, and antrum (100 U to 8 spots), corpus (100 U to 8 spots) and fundus (100 U to 8 spots) regions were injected intramuscularly. Patients were given a 1200-calorie low-carb diet and followed for 6 months. Results: Gastric BTX application was applied to 13 patients with a mean age of 40.9±5.2 (85% female), a mean body mass index(BMI) of 28.41±1.4 kg/m2 (26-31.6) and a mean excess weight of 10.1±3.6 kg. As a result of the 6-month follow-up, only 4 patients (30.8%) were able to lose more than 50% of their excess weight (6-15 kg). 6 patients (46.2%) could not lose any weight. There was an average decrease of 3.3 kg in the weight comparison to the patients before and after BTX application (p=0.03). A mean decrease of BMI was detected 1.17 kg/m2 (p=0.032). Conclusion: It was concluded that the application of gastric BTX for weight loss does not provide effective results.